Bioethical implications for sustainable rural development - Ahlert, Alvori (2023)
Considering the advances and technologies of conventional food production and the relationships already evidenced with devastating consequences for human health and the environment, this article brings discussions, through a bibliographic review, on the interdisciplinary genesis of bioethics and the discourse of authors of global environmental bioethics and sustainability: Van Renssealer Potter, Raquel Carson, Lutzemberg, Moltmann, Leonardo Boff and Jaime Breilh. The knowledge of bioethics within sustainable rural development, mainly related to the issue of pesticides is necessary when thinking about interdisciplinary environmental and health education. In addition to anato-physiological capacities, the human being is also a social y cultural being, with values and, equally, an environmental being, where the environment and the activities that exercises are totally connected to his health and quality of life.